2014
DOI: 10.1002/ana.24199
|View full text |Cite
|
Sign up to set email alerts
|

Frontoparietal cognitive control of verbal memory recall in Alzheimer's disease

Abstract: The results indicate that in AD, impaired responses of cognitive control networks during verbal memory recall are partly responsible for reduced recall performance. One action of symptom-modifying treatment is partially to reverse the abnormal function of frontoparietal cognitive control and temporal lobe memory networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 38 publications
1
37
0
Order By: Relevance
“…These sites form part of a broader cognitive control network, which supports sustained attention and goal-directed cognition, as well as a range of cognitively demanding tasks such as planning and problem-solving [67]. Recent studies indicate that disruption of this frontoparietal cognitive control network in AD adversely impacts episodic memory performance [68]. Our finding of bilateral angular gyri involvement irrespective of PM subtype in AD is therefore notable.…”
Section: Discussionmentioning
confidence: 53%
“…These sites form part of a broader cognitive control network, which supports sustained attention and goal-directed cognition, as well as a range of cognitively demanding tasks such as planning and problem-solving [67]. Recent studies indicate that disruption of this frontoparietal cognitive control network in AD adversely impacts episodic memory performance [68]. Our finding of bilateral angular gyri involvement irrespective of PM subtype in AD is therefore notable.…”
Section: Discussionmentioning
confidence: 53%
“…Such an analysis may partially emphasize some regions and ignore others. Two studies were ruled out, because their stereotactic results were not reported (Dhanjal et al, 2013; Dhanjal and Wise, 2014). Another two studies were excluded because they did not reveal any differences in activation between individual with aMCI and normal controls (Parra et al, 2013; Nicholas et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…These higher order executive functions are based on more fundamental frontal lobe functions, such as attention. Attention, is required for conscious recollection of autobiographic episodic memories (Dhanjal and Wise, 2014) and is diminished in AD (Kim et al, 2011). Therefore, attentional deficits in AD may contribute to autobiographical memory dysfunction.…”
Section: Cognitive and Neuroanatomical Underpinnings Of Autobiogramentioning
confidence: 99%